Development Of Web-Based Information System As A Media For Distribution Of Information On Vocational School Production Units To The Community - Perdana Novebrianto Kristi (Jurnal Mandiri IT, 2021)
The production unit in SMK is a means of learning and entrepreneurship for students. However, the production unit in SMK is currently still facing problems related to the marketing of products or services. This research was conducted with the objectives to: (1) assist SMK in disseminating production unit information to the general public online using a web-based SMK production unit information system. The results of this study are: (1) a web-based SMK production unit information system to help disseminate information on SMK production units to the wider community. the system has met the ISO/IEC 25010 software quality standard on usability aspect of 84.24% (very feasible), functional suitability aspect of 1 (all features can be implemented), reliability aspect of successful session 100%, successful pages 100%, and 100% successful hits (exceeding Telcordia standards), PageSpeed ​​efficiency aspect is 93.33% (Grade A) Yslow is 90.16% (Grade A) page load time is 3.06, and maintainability aspect has Maintainability value (2) the system has met the ISO/IEC 25010 software quality standard on usability aspect of 84.24% (very feasible), functional suitability aspect of 1 (all features can be implemented), reliability aspect of successful session 100%, successful pages 100%, and 100% successful hits (exceeding Telcordia standards), PageSpeed ​​efficiency aspect is 93.33% (Grade A) Yslow is 90.16% (Grade A)), and maintainability aspect has Maintainability value. Index 90.72 (easy to maintain). a web-based SMK production unit information system to help disseminate information on SMK production units to the wider community. the system has met the ISO/IEC 25010 software quality standard on usability aspect of 84.24% (very feasible), functional suitability aspect of 1 (all features can be implemented), reliability aspect of successful session 100%, successful pages 100%, and 100% successful hits (exceeding Telcordia standards), PageSpeed ​​efficiency aspect is 93.33% (Grade A) Yslow is 90.16% (Grade A) page load time is 3.06 seconds (less than 10 seconds), and maintainability aspect has Maintainability value. Index 90.72 (easy to maintain).